Long-term efficacy and feasibility of levonorgestrel-releasing intrauterine device use in patients with adenomyosis. Issue 22 (29th May 2020) - Song, Soo Youn; Lee, Sun Yeul; Kim, Hye Yun; Park, Dan Bit; Kim, Da Eun; Lee, Ki Hwan; Lee, Siyeo; Yang, Jung Bo; Yoo, Heon Jong
Abstract : Abstract: To evaluate the efficacy and feasibility of levonorgestrel-releasing intrauterine device (LNG-IUD) use longer than 5 years in women with adenomyosis. Data were retrospectively collected from patients who were treated with LNG-IUD longer than 5 years at the Chungnam National University hospital for adenomyosis diagnosed with ultrasonography from January 2006 to November 2013. A total of 131 patients who were diagnosed with adenomyosis had treated with LNG-IUD longer than 5 years. The mean duration of keeping 1 device without replacement was 58.35 ± 15.98 months, and total duration of LNG-IUD treatment was 83.86 ± 23.88 months. A total of 51 patients stopped using LNG-IUD after 5 years and the mean age at the time of LNG-IUD removal was 52.46 ± 6.9. LNG-IUD treatment had a significant effect on both menorrhagia and dysmenorrhea starting from the first month of insertion ( P < .01), which persisted until 6 years when the effect started to plateau. The decrease in uterine volume was not consistent during the treatment period. The uterine volume decreased significantly only in the first and second year of LNG-IUD treatment and then from eighth to tenth year of LNG-IUD treatment ( P < .05). Adverse events after insertion of LNG-IUD decreased significantly after 5 years. LNG-IUD treatment longer than 5 years is an effective and feasible method for patients diagnosed with adenomyosis.